Depresja dzieci i młodzieży jako skutek problemów osobniczego i społecznego rozwoju - Ćwikliński, Andrzej (Rocznik Pedagogiczny, 2021)
The article deals with the issue of depression in children and adolescents as a shortcut to problems of individual and social development. It presents the concept of depression and its typologies, showing depression as a disease increasingly common among children and adolescents. The biological and social causes of depression among young adolescents are indicated and other sources of depressive behaviors are also described. A particular role of the family in overcoming the symptoms of depres- sion is highlighted.